2006
DOI: 10.1021/es061397v
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Dissolved Carbonate Species on the Degradation of Trichloroethylene by Zerovalent Iron

Abstract: The effect of different concentrations of total inorganic carbon (TIC) and flow rates on the reactivity of iron metal with trichloroethylene (TCE) was studied in column experiments to verify whether concentration or mass flux of TIC is the major key parameter for barrier performance. First-order rate coefficients (kobs) for TCE degradation vary initially between 0.15 and 0.32 h-' and are positively related to TIC influent concentration. Maximal kobs were reached after 164 and 591 PV, varied between 0.55 and 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…Corrosion rates obtained from both static (Reardon, 1995(Reardon, , 2005 and continuous column experiments (Kamolpornwijit and Liang, 2006;Parbs et al, 2007) can therefore not be used for comparison between different experimental setups with different iron amounts. Filter dimensions have an effect on corrosion rate: The longer a column the lower are averaged corrosion rates.…”
Section: Estimated Corrosion Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Corrosion rates obtained from both static (Reardon, 1995(Reardon, , 2005 and continuous column experiments (Kamolpornwijit and Liang, 2006;Parbs et al, 2007) can therefore not be used for comparison between different experimental setups with different iron amounts. Filter dimensions have an effect on corrosion rate: The longer a column the lower are averaged corrosion rates.…”
Section: Estimated Corrosion Ratesmentioning
confidence: 99%
“…Parbs et al (2007) reported on gas generation in continuous column experiments starting gas collection at day 60. They suggested that mass flux of total inorganic carbon (TIC) determines corrosion rates and reduction of chlorinated hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion experiments with granular iron have indicated that the formation of mineral precipitates affect the long-term reactivity of PRB (Kober et al, 2002;Klausen et al, 2003;Kohn et al, 2005;Parbs et al, 2007;Weber et al, 2013). In particular, mainly iron hydroxide carbonate (chukanovite, Fe 2 CO 3 (OH) 2 ) is formed in the presence of carbonate on the iron surface (Ruhl et al, 2011) and influences significantly the reactivity (Jeen et al, 2006;Lee and Wilkin, 2010;Ruhl et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mainly iron hydroxide carbonate (chukanovite, Fe 2 CO 3 (OH) 2 ) is formed in the presence of carbonate on the iron surface (Ruhl et al, 2011) and influences significantly the reactivity (Jeen et al, 2006;Lee and Wilkin, 2010;Ruhl et al, 2012). High concentrations of inorganic carbon increase not only the dehalogenation rates of chlorinated groundwater contaminants but also the inhibition of reactive sites in the long-term (Parbs et al, 2007). Based on results of field-scale PRBs, Lee and Wilkin (2010) calculated the phase stability of siderite (FeCO 3 ), chukanovite and ferrous hydroxide in a Fe(II)eCO 2 eH 2 O-system.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Corrosion products formed on the surface of Fe 0 through chemical reactions have major effects on the reactivity, porosity, permeability, and consequent longevity of Fe 0 -PRB technology. [5][6][7][8] Several researchers [7][8][9][10][11] have attempted to characterize the surface precipitate that is generated in laboratory or field studies, and the corrosion products on the surface of Fe 0 was found to include aragonite, calcite, iron carbonate (siderite), sulfides and oxides (goethite, lepidocrocite, magnetite, and hematite), hydroxide, hydroxy oxides, and other intermediate products. Other efforts [12][13][14][15] have discovered the presence of the Fe 2 (OH) 2-CO 3 , which is a frequently detected secondary mineral precipitate in bicarbonate (carbonate) solutions and is overlooked for a long time.…”
Section: Introductionmentioning
confidence: 99%